Dynamics and monetary policy in a fair wage model of the business cycle - David de la Croix; Gregory de Walque; Raf Wouters (European Central Bank (ECB), 2007)
We first build a fair wage model in which effort varies over the business cycle. This mechanism decreases the need for other sources of sluggishness to explain the observed high inflation persistence. Second, we confront empirically our fair wage model with a New Keynesian model based on the standard assumption of monopolistic competition in the labor market. We show that, in terms of overall fit, the fair wage model outperforms the New Keynesian one. The extension of the fair wage model with lagged wage is judged insignificant by the data, but the extension based on a rent sharing argument including firm's productivity gains in the fair wage is not. Looking at the implications for monetary policy, we conclude that the additional trade-off problem created by the inefficient real wage behavior significantly affect nominal interest rates and inflation outcomes.
Keywords: E4; E5; 330; efficiency wage; effort; Inflation persistence; monetary policy; Arbeitsmarkttheorie; Effizienzlohn; Rawls-Gerechtigkeitstheorie; Neoklassische Synthese; Theorie